Precipitation chemistry and atmospheric nitrogen deposition at a rural site in Beijing, China. (15th February 2020) - Xu, Wen; Wen, Zhang; Shang, Bo; Dore, Anthony J.; Tang, Aohan; Xia, Xiaoping; Zheng, Aihua; Han, Mengjuan; Zhang, Lin; Zhao, Yuanhong; Zhang, Guozhong; Feng, Zhaozhong; et al.
Abstract: Precipitation chemistry and atmospheric nitrogen (N) deposition are of great concern worldwide due to their close relationships with air quality and impacts on ecosystems. However, evaluation of the chemical composition of precipitation and N deposition flux in rural areas of Beijing has received little attention to date. This paper presents the chemical constituents, possible sources and wet deposition fluxes of water-soluble ions (NH4 +, NO3 −, SO4 2−, Cl −, Na +, K +, Ca 2+, Mg 2+ ) in precipitation samples collected during 2017–2018 at a rural site located at northwest of Beijing city; meanwhile, dry deposition of reactive N species (gaseous ammonia, nitrogen dioxide, nitric acid, and particulate ( p ) NH4 + and NO3 − ) were also quantified. During this 2-year period, the volume-weighted mean (VWM) pH of precipitation was 6.73, and all samples had pH values above 6.0. The VWM electric conductivity of precipitation and the mean sum of all measured ions was 43.8 μS cm −1 and 591.9 μeq L −1, respectively, indicating a significant impact of atmospheric pollution. Ca 2+ and NH4 + were the dominant neutralizing species for precipitation acidity. Positive matrix factorization analysis further confirmed five sources for water-soluble ions, including sea salt aging, secondary formation, agriculture, crust, and biomass burning. The annual mean wet N deposition was 4.6, 3.4 and 8.0 kg N ha −1 yr −1 for NH4 +, NO3 − and total inorganic N, respectively. The total dry N deposition was dominated by gaseous ammonia (11.5 kg N ha −1 yr −1 ). The total N deposition (wet plus dry) was 27.7 kg N ha −1 yr −1, where dry deposition contributed to 75% and wet deposition 25% of the total. The simulations from the GEOS-Chem model indicate that agricultural (fertilizer use and livestock) and nonagricultural sources (industry, power plant, and transportation) are both important contributors to total N deposition. These results could be useful in evaluating/developing emission control policies to protect the eco-environment in Beijing. Highlights: Precipitation chemistry and nitrogen (N) deposition were investigated in Beijing. The pH values of precipitation samples were all above 6.0 and averaged 6.7. Ion source was sea salt, secondary source, agriculture, crust, and biomass burning. Total N deposition was 27.7 kg N ha −1 yr −1, of which 75% was from dry deposition. Agricultural and nonagricultural sources contributed equally to total N deposition.